Establishment of SIAISi021-A, an induced pluripotent stem cell (iPSC) line from a 71-year-old Chinese Han male with Alzheimer’s Disease (AD) having two copies of APOE4/4 allele - Yanfei Ding; Haijuan Chen; Jian Zhao; Ying Wang; Yulei Deng (Stem Cell Research, 2022)
A 71-year-old Han male from China contributed peripheral blood mononuclear cells (PBMCs). Non-integrative Sendai viral vectors containing reprogramming factors OCT4, KLF4, SOX2 and C-MYC were used to reprogram PBMCs. Pluripotency makers confirmed the pluripotency of transgene-free induced pluripotent stem cell (iPSC). The ability of iPSC to spontaneously differentiate three germ layers in vitro confirmed the pluripotency of iPSC. The iPSC line displayed a normal karyotype. The newly generated human iPSC SIAISi021-A can be used for studying further disease mechanisms of Alzheimer’s Disease (AD).